(untitled) (مجلة جامعة بابل للعلوم الانسانية, 2020)
The study aims to reveal the effectiveness of a selective counseling program for positive psychological support to reduce Cyberbullying among secondary school students in Babylon Governorate. It is applied to a sample of (60) secondary school students in Babylon governorate with an average age of (16.5) years old and a standard deviation of (2.87) years. The semi-experimental approach was used, and Cyberbullying measure is applied, as well as the selective pilot program. The study has found that the the selective counseling program based on positive psychological support to reduce Cyberbullying among secondary school students in Babylon Governorate is effective, as it has found statistically significant differences between the pre and post application of the study in favor of post application.